Using administrative data to examine mental health service use among post-secondary students in Alberta, Canada - Navjot Lamba; Robert Jagodzinski (International Journal of Population Data Science, 2018)
Introduction Poor mental health among post-secondary students has been on the rise, and as such, has become a growing concern for the Alberta government. Alberta’s major post-secondary institutions have emphasized the need for evidence that would improve mental health supports for students troubled by mental health issues.